Kecernaan Serat dan Fermentasi Kulit Buah dan Pelepah Nipah Menggunakan Mikro Organisme Lokal (MOL) - Suryadi Suryadi; Ubaidillah Ubaidillah; Farizaldi Farizaldi (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims: to determine the appropriate length of fermentation time for   nipah fruit skin and nipah midrib so that the nutritional value and digestibility of  cellulose and hemicellulose are increased. The study used a completely randomized design with 2 factor, namely: the type of material and the length of time of fermentation and was repeated 3 times. The first factor is the type of material: nipah fruit skin and palm fronds. Factor II, namely the lenght of fermentation time : 5 days, 10 days, 15 days and 20 hari hearts. Variables measured were crude fiber content, crude protein, cellulose digestibility and hemicellulose digestibility. The results showed that the digestibility of cellulose and hemicellulose digestibility of nipah fruit peels and palm fronds were significantly different (P<0,05) but the crude fiber and crude protein  (MOL).  In general, the digestibility of cellulose and hemicellulose inscreases with increasing fermentation time. The best digestibility occurred at 15 days of fermentation time for cellulose digestibility 64,69% and hemicellulose digestibility 72,43%. The interaction between nipah fruit skin and fermentation time of 20 days showed optimal results on hemicellulose digestibility.